2018
DOI: 10.1042/bsr20181065
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 mediates cell migration and invasion of gastric cancer

Abstract: Gastric cancer (GC) is a common highly aggressive malignant tumor in worldwide. Ubiquitin-like with PHD and ring-finger protein 1 (UHRF1) has a key role in several kinds of cancers development. However, the biology effect of UHRF1 on the tumorigenesis of GC remains unclear. In this research, the role of UHRF1 in the growth, migration, invasion and apoptosis and the underlying mechanisms were investigated in MGC803 and SGC7901 cells. The UHRF1 knockdown MGC803 and SGC7901 cell lines were used to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…UHRF1 antagonism is emerging as a therapeutic strategy in cancer (18, 19, 2932). Recent genetic studies suggest that inhibition of the UHRF1 SRA–DNA interaction is a strategy for inhibiting tumor suppressor gene silencing in colon cancer cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…UHRF1 antagonism is emerging as a therapeutic strategy in cancer (18, 19, 2932). Recent genetic studies suggest that inhibition of the UHRF1 SRA–DNA interaction is a strategy for inhibiting tumor suppressor gene silencing in colon cancer cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…The protein UHRF1 encodes a hub protein that integrates epigenetic information. In the study of gastric cancer, the researchers found that the high expression of this gene would enhance the invasion and proliferation of tumor 40 …”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR was done with Brilliant III Ultra-Fast SYBR Green (Agilent) with ACTB gene as homeobox gene. We used BCL-2 10 , BIRC5 (survivin) 11,12 , Bax 9 , p53 13 , ABCB1 14 , UHRF1 15 , and DNMT1 16 genes for apoptotic effects after thymoquinone and beta-sitosterol treatment.…”
Section: Gene Expressions Assaymentioning
confidence: 99%
“…Previous studies revealed that some DEGs are responsible for carcinoid lesions in the stomach, which are induced by elevations of gene expression such as BCL-2 10 , BIRC5 (survivin) 11,12 , Bax 9 , p53 13 , ABCB1 14 , UHRF1 15 , and DNMT1 16 . These genes are involved by the Hippo BIRC5 pathway, p53 signaling pathway, intrinsic apoptotic pathway that interacts with XIAP and DIABLO leading to caspase-3 and caspase-9 inactivation, or regulators of apoptosis, WNT pathway, UHRF1-dependent regulation, and DNA methyltransferase pathway.…”
Section: Introductionmentioning
confidence: 99%